Europeanizing the Danish School through National Testing: Standardized Assessment Scales and the Anticipation of Risky Populations. (March 2020) - Ratner, Helene
This paper explores "the peopling of Europe through data practices" in relation to standardized testing of students in Denmark. Programme for International Student Assessment (PISA) is a central component of Danish and European education infrastructures. In Denmark, mediocre PISA results spurred the introduction of national testing. With inspiration from Michel Foucault's notion of biopolitics, this paper analyzes how complementary Danish national test assessment scales make up population objects and student subjects and how these scales are aligned with European and transnational standards. A norm scale, standardized against the European Credit Transfer System (ECTS) grading scale, enacts a population whose performance can be tracked over time. A criteria scale introduces categories describing skills and enacts a moving student subject whose progression can be tracked. This paper argues that the three assessment scales enact the student population as bound to the nation and as simultaneously constituted in relation to transnational European categories and imaginaries of competition. As part of this, this paper discusses how the national test and PISA are used to single out students of non-European background, anticipated to be low PISA achievers and nonparticipants in a European knowledge economy.